The management of iron deficiency in inflammatory bowel disease – an online tool developed by the RAND/UCLA appropriateness method. Issue 9 (17th September 2013) - Reinisch, W.; Chowers, Y.; Danese, S.; Dignass, A.; Gomollón, F.; Haagen Nielsen, O.; Lakatos, P. L.; Lees, C. W.; Lindgren, S.; Lukas, M.; Mantzaris, G. J.; Michetti, P.; et al.
Summary Background Iron deficiency is a common and undertreated problem in inflammatory bowel disease (IBD). Aim To develop an online tool to support treatment choice at the patient‐specific level. Methods Using the RAND/UCLA Appropriateness Method (RUAM), a European expert panel assessed the appropriateness of treatment regimens for a variety of clinical scenarios in patients with non‐anaemic iron deficiency (NAID) and iron deficiency anaemia (IDA). Treatment options included adjustment of IBD medication only, oral iron supplementation, high‐/low‐dose intravenous (IV) regimens, IV iron plus erythropoietin‐stimulating agent (ESA), and blood transfusion. The panel process consisted of two individual rating rounds (1148 treatment indications; 9‐point scale) and three plenary discussion meetings. Results The panel reached agreement on 71% of treatment indications. 'No treatment' was never considered appropriate, and repeat treatment after previous failure was generally discouraged. For 98% of scenarios, at least one treatment was appropriate. Adjustment of IBD medication was deemed appropriate in all patients with active disease. Use of oral iron was mainly considered an option in NAID and mildly anaemic patients without disease activity. IV regimens were often judged appropriate, with high‐dose IV iron being the preferred option in 77% of IDA scenarios. Blood transfusion and IV+ESA were indicated in exceptional cases only. Conclusions The RUAM revealed high agreement amongst experts on the management of iron deficiency in patients with IBD. High‐dose IV iron was more often considered appropriate than other options. To facilitate dissemination of the recommendations, panel outcomes were embedded in an online tool, accessible via http://ferroscope.com/.